THE STUDYOF PHYTOCHEMICAL CHARACTERS OF EROVSKIA ABROTANOIDES IN KASHAN - H. Azarnivand; M. Alikhah Asl; M. Jafari; H. Dastmalchi; J. Safari; H. Joneidi Jafari (Desert, 2005)
The studies conducted on plants grown in Kashan have showed the presence of abundant valuable industrial - medicinal plants. Unforlunately, a lot of these plants are removed as weed or grazed by livestock because of Lack of inhabitants' ignorance of their using and mismanagement. - Perovskia abrotanoides is of Lamiaceae family. The natural habitat of this plant is mostly near waterways, the beds and borders of seasonal rivers and mountainous ravines, namely the watersheds of south and southeast of Kashan .It is also seen in the borders of gardens and farms in these areas. This plant is mostly seen at the elevations 1500 - 2700 m. Its flowers, leaves and stems contain a lot of essence that can be used in medicine industry. In order to study this plant phytochemically, 6 areas (points) were selected. The average amount of plants' essence obtained from these 6 investigated areas was 4/5 cc(1/44%) in Ferizhend , 3/8 cc(1/1%)in Abyaneh, 2/8 cc(1/12%) in Chimeh, 219 cc(0/93%) in Ghohroud, 1/9 cc(0/61%) in Totmaj and 2/3 cc(O/74%) in Jahagh. Moreover determining the amount of existent essence in plant, we proceeded to find four plant materials: Saponin, Alkaloid, Tannin, Flavanoid. The amount of each material in plant was defined qualitatively in which the amount of saponin was considerable.